Letting Go, Without Losing Coherence: How Local Agency and Donor Accountability Can Coexist - Guerzovich, Florencia (TWP CoP, University of Birmingham, 2026)
Despite widespread endorsement of locally led development, donor agencies still struggle to translate local agency into cumulative change. Donor discourse increasingly emphasises localisation and community leadership, yet operational arrangements remain structured around upward compliance. The practical question is how local agency and institutional accountability can work together so that locally generated insights lead the way while portfolio coherence is maintained. This paper examines a form of connective work that helps make this co-existence possible. Drawing on the author’s more than 20 years’ experience as a practitioner and evidence from over 150 documented cases across sectors and regions, it focuses on invisible weavers – actors who keep cooperation moving under constraint by connecting fragmented institutions, routing insights across levels, and sustaining continuity when conditions change. These functions are often essential to maintaining cooperation, insights, and continuity across fragmented actors and institutions, yet they remain largely unrecognised in formal programme design, costing, and evaluation. Despite this, donors’ informal routines allow them to act on these insights, albeit in ad hoc ways. The paper addresses three practical questions: how such actors can be recognised, how their effectiveness and resilience can be assessed, and how donors can support this connective work more intentionally without formalising it into compliance. It traces how donor staff and local counterparts use judgement, continuity, and low-overhead practices to carry locally generated insights into organisational decisions. By reframing accountability as portfolio reliability and making these patterns visible, the paper shows that donors can ‘let go’ of rigid control without losing systemic coherence. It concludes with three practical ways to make these existing ‘workarounds’ more intentional and fundable, ensuring that local intelligence leads to durable change rather than having to re-set with every project cycle.

The end of reporting - Sutton, Amy (2024)
After eight years, I am leaving Porticus. From January 2025, I'll be starting a new chapter - working in a freelance capacity to support systems change efforts through strong learning, evaluation and strategy. Having worked with the amazing Porticus UK team for the first four years, I moved to Amsterdam in 2020 to work in the central strategy and learning team, supporting colleagues around the globe to embed strategy, evaluation and learning in their work. I loved this work. I learned a huge amount about social justice, and about how philanthropy can most effectively support the many fights for change needed today. I will miss the passion and commitment of so many people I feel privileged to work with - too many to name here. One of the pieces of work I am most proud of is the design and introduction of a new practice of learning between Porticus and its partner grantees, ending the burden of written reporting. I will always appreciate my colleagues’ appetite for innovation and to living out their values with this work. Getting rid of reporting may sound radical, but static reporting about what happened and what was done doesn’t fit with a systems change approach. If we trust our grantee partners, let’s focus on working and learning with them, about what matters. Reporting about outputs, activities, actual spend vs anticipated spend, will not help us shift systems. Learning together about what’s changing, why, how, and how can we adjust or adapt as a result of this insight and learning, in real time, will. As I leave Porticus, I will be taking this approach to learning with me. And as I do so, I would like to urge the philanthropy sector to challenge itself and explore how the systems we use for evaluation, learning and reporting can be made more fit for purpose for system change, less burdensome and more equitable. Here is a reflection piece I’ve written about why this learning practice. I offer this as a personal reflection and share it in the hope that more foundations and funders will think about doing their reporting differently - and ideally, not doing reporting at all…

Foreign Aid and Its Unintended Consequences - Koch, Dirk-Jan (Routledge, 2023)
Foreign aid and international development frequently bring with it a range of unintended consequences, both negative and positive. This book delves into these consequences, providing a fresh and comprehensive guide to understanding and addressing them. The book starts by laying out a theoretical framework based on complexity thinking, before going on to explore the ten most prevalent kinds of unintended effects of foreign aid: backlash effects, conflict effects, migration and resettlement effects, price effects, marginalization effects, behavioural effects, negative spillover effects, governance effects, environmental effects, and ripple effects. Each chapter revolves around a set of concrete case studies, analysing the mechanisms underpinning the unintended effects and proposing ways in which policymakers, practitioners, and evaluators can tackle negative side effects and maximize positive side effects. The book also includes personal testimonies, a succinct overview of unintended effects, and suggestions for further reading. Providing a clear overview of what side effects to anticipate when planning, executing, and evaluating aid, this book will be an important resource for students, development practitioners, and policymakers alike.

The Big Con: How the Consulting Industry Weakens our Businesses, Infantilizes our Governments and Warps our Economies - Mazzucato, Mariana; Collington, Rosie (Allen Lane, 2023)
There is an entrenched relationship between the consulting industry and the way business and government are managed today which must change.Mariana Mazzucato and Rosie Collington show that our economies' reliance on companies such as McKinsey, Boston Consulting Group, Bain & Company, PwC, Deloitte, KPMG and EY stunts innovation, obfuscates corporate and political accountability and impedes our collective mission of halting climate breakdown.The 'Big Con' describes the confidence trick the consulting industry performs in contracts with hollowed-out and risk-averse governments and shareholder value-maximizing firms. It grew from the 1980s and 1990s in the wake of reforms by both the neoliberal right and Third Way progressives, and it thrives on the ills of modern capitalism, from financialization and privatization to the climate crisis. It is possible because of the unique power that big consultancies wield through extensive contracts and networks - as advisors, legitimators and outsourcers - and the illusion that they are objective sources of expertise and capacity. To make matters worse, our best and brightest graduates are often redirected away from public service into consulting. In all these ways, the Big Con weakens our businesses, infantilizes our governments and warps our economies.Mazzucato and Collington expertly debunk the myth that consultancies always add value to the economy. With a wealth of original research, they argue brilliantly for investment and collective intelligence within all organizations and communities, and for a new system in which public and private sectors work innovatively for the common good. We must recalibrate the role of consultants and rebuild economies and governments that are fit for purpose.

How Big Things Get Done: The Surprising Factors Behind Every Successful Project, from Home Renovations to Space Exploration - Flyvbjerg, Bent; Gardner, Dan (Macmillan, 2023)
World expert Bent Flyvbjerg and bestselling author Dan Gardner reveal the secrets to successfully planning and delivering ambitious projects on any scale.Nothing is more inspiring than a big vision that becomes a triumphant new reality. Think of how Apple’s iPod went from a project with a single employee to an enormously successful product launch in eleven months. But such successes are the exception. Consider how London’s Crossrail project delivered five years late and billions over budget. More modest endeavours, whether launching a small business, organizing a conference, or just finishing a work project on time, also commonly fail. Why?Understanding what distinguishes the triumphs from the failures has been the life’s work of Oxford professor Bent Flyvbjerg. In How Big Things Get Done, he identifies the errors that lead projects to fail, and the research-based principles that will make yours succeed:- Understand your odds. If you don’t know them, you won’t win.- Plan slow, act fast. Getting to the action quick feels right. But it’s wrong.- Think right to left. Start with your goal, then identify the steps to get there.- Find your Lego. Big is best built from small.- Master the unknown unknowns. Most think they can’t, so they fail. Flyvbjerg shows how you can.Full of vivid examples ranging from the building of the Sydney Opera House to the making of the latest Pixar blockbusters, How Big Things Get Done reveals how to get any ambitious project done – on time and on budget.

Celebrating Adaptive Delivery: A View from the Frontline in Myanmar - Barnes, Katrina; Lonsdale, Jane (Institute of Development Studies, 2023)
The conversation on adaptive management has grown fast amongst development actors. These conversations often focus on designing, commissioning, and managing large-scale development programmes. Exactly how this impacts the frontline, the implementers, and day-to-day project delivery is still being debated. Yet, perspectives drawn directly from practice are often largely missing within these debates. This paper is written by two development practitioners. Through this paper, we reflect on the difference between adaptive management and adaptive delivery, and how this interacts with risk and aid accountability, particularly in contexts of fragility. Drawing on examples of Oxfam in Myanmar work and our personal insights in relation to delivering programming across humanitarian, peace-building, and development, we suggest that in complex, conflict-affected, and highly political environments adaptive delivery already happens far more regularly than is currently recognised, as a necessity to get activities delivered. However, it happens despite the system, not because of it, and is therefore often hidden and carried out ‘under the radar’ rather than celebrated as a success in difficult environments. This paper was written in 2019, before the military seized control of Myanmar in February 2021. Whilst it draws on examples from pre-2021 Myanmar to illustrate real life cases, it is a contribution to a broader global debate on adaptive management in practice, specifically in fragile contexts. This is not specifically aimed at practitioners working in Myanmar at present, who are now working in a protracted crisis. This paper makes tangible recommendations on steps that donors, international non-governmental organisations, local staff, and partners could take to promote a system of encouraging and celebrating adaptability in programme delivery in fragile contexts.
Accepted: 2023-02-02T14:48:03Z

Achieving disability inclusive employment – Are the current approaches deep enough? - Shaw, Jackie; Wickenden, Mary; Thompson, Stephen; Mader, Philip (Journal of International Development, 2022)
Diverse approaches to promoting disability inclusive employment aim to transform workplaces into truly inclusive environments, usually with intervention strategies targeting two main groups: employers and jobseekers with disabilities. However, they do not always consider other relevant stakeholders or address the relationships and interactions between diverse actors in the wider social ecosystem. These approaches often neglect deeper ‘vexing’ difficulties which block progress towards disability inclusive work environments. Most interventions rightly embrace hegemonic ‘social models of disability’ and use human rights arguments but may neglect entrenched structural factors. Disability inclusive employment is complex, with unaddressed invisible aspects that continue to limit progress. We explore some key relevant disability concepts and then interrogate evidence from the ‘Inclusion Works’ programme working in four middle- and low-income countries, considering some intractable barriers underlying the slow movement towards inclusive employment. Finally, we propose that a more participatory action orientated approach involving disabled people and others is needed to both generate deeper understanding and provide pathways towards new solutions to obstinate problems through progressive action learning processes in context. Programmatic interventions that work across the levels of the ecosystem and address power relations and interactions between stakeholders could lead to more substantial forms of disability inclusive employment.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/jid.3692

Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid delivery more adaptive, relying on principles such as context sensitivity, flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering social transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implications in practice. Purpose The article aims to provide evidence on an adaptive project and demonstrate how the social transformative and political nature of adaptive development management is rendered technical and depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy framework that is implemented through CSOs in Uganda and Vietnam. Data were collected by means of interviews, participant observation and document analysis. Findings We find that, in practice, the social transformative policy framework is competing with managerial logics. We compare this process with the depoliticization of the Paris Declaration on Aid Effectiveness, finding striking similarities. By using practice theory, we show how managerialism remains the dominant paradigm in the civil society aid sector, fuelling the “anti-politics machine.” Policy implications The article shows that policy frameworks do not always work as intended. Donors should therefore not only change policy frameworks, but also start addressing institutional and operational requirements.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12630

Lives Amid Violence: Transforming Development in the Wake of Conflict - Schomerus, Mareike (2022)
Violent conflict and its aftermath are pressing problems, particularly for international development initiatives. However, the results of development in conflict contexts have generally been disappointing and their preventative potential thus questionable. Available Open Access, Lives Amid Violence argues that this is because practitioners adhere to a mental model that emphasises linearity, certainty, and causality, assuming that violence is best addressed through work plans that deliver state-building, stabilisation and services. Based on ten years of multi-method research from, in, and on conflict-affected countries, this book challenges this approach.Drawing on a significant collaborative body of scholarship, this work puts forward original and generalizable conclusions about how lives amid violence persist, offering an invitation to abandon restricting mental models and to embrace creative ways of thinking and working. These include paying attention to the long-term effects of conflict on individual behaviour and decision-making, the social realities of economic life, the role service delivery plays in negotiations between citizens and states, and to creating meaningful relationships. Transformation also requires reflection and therefore the book concludes with constructive suggestions on how to practice these insights to better support those whose lives are shaped by violence.More details are available at www.transformingdevelopment.orgThe eBook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com.

Project facilitation as an active response to tensions in international development programmes - Lannon, John; Walsh, John N. (International Journal of Project Management, 2020)
This paper examines the tension within international development programmes between traditional task-oriented approaches to development and the wider view of programmes as sites for adaptability and learning. It characterises it as a set of inter-related tensions between recursive and adaptive tendencies that exist at individual actor, programme and institutional levels. Drawing on a multiple interpretive case study of partnership based programmes between an international non-government organisation and local partners in three countries, it looks at how these tensions play out in practice. Based on the findings, it proposes an active response to the tensions called project facilitation. This is an adaptive and co-created process that incorporates local experience and practice based knowledge to achieve strategic goals, while utilising recognised project management practices to achieve agreed outcomes. By adopting active responses to the tensions that exist within programmes it offers greater potential for effective delivery of long term benefits than the more typical defensive response strategies. Project facilitation is consistent with the social constructionist view of programmes and programme management but broadens our understanding by emphasising the need to actively consider how the tensions inherent in programmes are responded to.
Keywords: Adaptive management; International development; Non-governmental organisations; Partnership; Programme management; Project facilitation; Tensions

Webinar - Sustainability Ready: what it takes to support & measure lasting change - Cekan, Jindra (Valuing Voices, 2020)
On June 24th under GLocal’s UNConference, “Co-creating our future stories of hope and action”, Jindra Cekan, Holta Trandafili, and Isabella Jean presented their work on sustainability evaluations and exit strategies via local voices. We chaired a 2-hour discussion session on the following topics: Sustainability of global development projects and exit from them, The importance of valuing local partners’ and participants’ voices, How to embed ex-post evaluation of sustainability into the project cycle, How expectations, benchmarking, and early joint planning in exit strategies, as well as considering long-term ownership & relevance will support projects to be sustained locally, including questioning who will maintain results, Considering power dynamics between donors and ultimate ‘beneficiaries’ and the value of the impact of the project from a variety of perspectives, and more Here is the recording of our presentation or see just the PowerPoint presentation. We harvested lessons from our three presentations: Jindra Cekan: · Fear of learning about failure in our global development industry – INGOs are “waiting for a successful enough project” to commission ex-post project sustainability evaluation · It needs to be a culture of learning, not a culture of success. · Lack of transparency in sharing program evaluation results with communities and local government is widespread, and even more rarely do we come back after many years and share learnings · Participatory approaches are vital, listening to participants about sustained impacts is key · It is never attribution, always contribution. To isolate impacts, we need to look for project sites that haven’t had multiple other organizations overlapping through all phases. · Building sustainability planning throughout the project cycle is key – but often doesn’t happen Holta Trandafili: · Sustainability needs to be planned to be researched, including evaluating why or why not were project elements sustained, and why? What has the project done to enable communities to sustain improvements? · Expectations of sustainability need to be more modest (as most results are mixed good/bad) · We need to ask: How are you defining and measuring sustainability – for how long should the results last? Among how many participants? Have you set benchmarks for success? · We should expand your toolbox on methodology to investigate sustainability. Stories of success are one of a myriad of methods used, including mixed-methods, cost-benefit, etc. · Start with the need for learning not [just] accountability Isabella Jean: · Sustainability investigation/evaluation/learning should be mindful that this is NOT about projects. It is about people. · We have a system that focuses on gaps and needs to be filled vs. existing capacities’ structures to be reinforced. How can our work on measuring sustainability bring this to light and call it out, so that we change the norm? · Planning for sustainability requires the insight to integrate resources and experiences of outsiders with the assets and capacities of insiders to develop context-appropriate strategies for change If you would like to discuss this with any of us, please send us comments and we’re happy to respond. Thanks again to the G-Local UnConference team! Below please find our bios: Jindra Cekan/ova has worked in global development for 33 years focused on participatory design and M&E for global non-profits. She founded Valuing Voices 7 years ago. For details, see: Valuing Voices Founder Holta Trandafili is the Research, Learning, and Analytics Manager with World Vision US and has been leading field research, monitoring, and evaluation since 2007. She has led sustainability measurement studies for World Vision programs in Uganda, Kenya, Sri Lanka, India, Burma, and Bolivia. Her areas of expertise and interest include program and community groups’ sustainability measurements; agency-level measurements; empowerment approaches to development; integrated programming; local capacities for peace; gender analysis; and outcome monitoring. Currently, Mrs. Trandafili serves as an Advisory Committee member for InterAction’s Effectiveness and Program Evaluation Working Group and chairs one of the sub-working groups under The Movement for Community-led Development. Isabella Jean supports international and local organizations and funders to document promising practices, facilitate learning and strengthen capacities for conflict sensitivity, peacebuilding and humanitarian effectiveness. She has facilitated action research, collaborative learning and advisory engagements in over 25 countries, and serves as an advisor to policymakers, senior leadership and program teams. Isabella co-authored the book, Time to Listen: Hearing People on the Receiving End of Aid and developed practical guidance to support accountability to communities, listening and feedback loops, and responsible INGO exits. She teaches graduate-level courses on aid effectiveness, program strategies and M&E of peacebuilding at Brandeis University’s Heller School for Social Policy and Management. Previously, Isabella directed training at a community organizing network and conducted policy research for the Institute for Responsive Education, UNDP, and Coexistence International.

Simplexity² or: How I Learned to Stop Worrying and Love Complexity in Development - Prieto Martin, Pedr (2018)
This seminar is the fifth in a series that aims to share cutting edge thinking and research being done at IDS and the University of Sussex around how we practically capture and account for complexity across a variety of sustainable development contexts. Join us for a fascinating trip from Athens to Xiaogang where, assisted by Steve Jobs, Sun Tzu and Aristotle, and with the help of a series of memorable diagrams, we attempt to alchemise development’s complexity into… a simple living tree. The seminar aims to integrate into an accessible narrative notions from various disciplines related to complexity science –including psychology, philosophy, organisational development and software engineering– as a way to articulate essential complexity concepts. Insights emerging from our cluster’s research on Adaptive Management and on the use of Frontier Technologies for development are linked with ideas presented by Prof. Chambers, Burns, Scoones and Ang in the previous seminars, to explore what complexity means in practice for development professionals and how we can discern and handle it at best. About the Speaker Pedro Prieto Martín is a software engineer turned trans-disciplinary social scientist. Pedro’s academic background includes degrees in Computer Science, Business Administration, Philosophy, and Sociology from different Spanish universities. After working for years at Hewlett-Packard in Germany as the Technical Lead of a development team, he moved to Latin America, where for years he researched the application of ICT to improve local governance and promote social change. Before joining the Digital and Technology cluster he supported and researched, at the local level, the social mobilisation processes that resulted from the “indignados” movement in Spain and their use of ICT. At IDS, Pedro has investigated the drivers of adaptiveness in accountability interventions, as part of MAVC. He now coordinates the learning component of DFID’s “Frontier Technologies Livestreaming (FTL)” programme, which has been recently awarded UK’s Civil Service Award for Innovation. FTL supports DFID country offices to experiment with the use of emerging technologies to address development challenges.

Navigation by Judgment: Why and when Top Down Management of Foreign Aid Doesn't Work - Honig, Dan (Oxford University Press, 2018)
Foreign aid organizations collectively spend hundreds of billions of dollars annually, with mixed results. Part of the problem in these endeavors lies in their execution. When should foreign aid organizations empower actors on the front lines of delivery to guide aid interventions, and when should distant headquarters lead? In Navigation by Judgment, Dan Honig argues that high-quality implementation of foreign aid programs often requires contextual information that cannot be seen by those in distant headquarters. Tight controls and a focus on reaching pre-set measurable targets often prevent front-line workers from using skill, local knowledge, and creativity to solve problems in ways that maximize the impact of foreign aid. Drawing on a novel database of over 14,000 discrete development projects across nine aid agencies and eight paired case studies of development projects, Honig concludes that aid agencies will often benefit from giving field agents the authority to use their own judgments to guide aid delivery. This "navigation by judgment" is particularly valuable when environments are unpredictable and when accomplishing an aid program's goals is hard to accurately measure. Highlighting a crucial obstacle for effective global aid, Navigation by Judgment shows that the management of aid projects matters for aid effectiveness.
Google-Books-ID: GT5MDwAAQBAJ

Aiming at the Wrong Targets: The Domestic Consequences of International Efforts to Build Institutions - Buntaine, Mark T.; Parks, Bradley C.; Buch, Benjamin P. (International Studies Quarterly, 2017)
We explain why international development organizations have had so little success building and reforming public sector institutions in developing countries. They often fail despite their apparently strong commitment to achieving measurable results and extraordinary amounts of time, money, and effort. We demonstrate that, when donors and lenders make access to financing contingent upon achievement of performance targets, recipient countries tend to choose easy and shallow institutional targets. These targets measure the organization of public sector institutions, rather than their effectiveness at addressing public problems. Such targets provide countries with low-cost opportunities to signal commitment to institution-building to international development organizations. We demonstrate the explanatory and predictive power of our argument in the context of a sector of World Bank lending—environment and natural resource management—that focuses heavily on improving public sector institutions.

Matrixing Aid: The Rise and Fall of 'Results Initiatives' in Swedish Development Aid - Vähämäki, Janet (Stockholm Business School, Stockholm University, 2017)

Moving from Real-Time Data to Real-Time Programs - Lee, Panthea (Reboot, 2016)
How can we avoid drowning in data to actually make better decisions?
Keywords: IMPORTANT

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.

Perverse Payment by Results: frogs in a pot and straitjackets for obstacle courses - Chambers, Robert (IDS - Participation, Power and Social Change, 2014)
Posts about Robert Chambers written by idsppsc

The Good Project: Humanitarian Relief NGOs and the Fragmentation of Reason - Krause, Monika (University of Chicago Press, 2014)
NGOs set out to save lives, relieve suffering, and service basic human needs. They are committed to serving people across national borders and without regard to race, ethnicity, gender, or religion, and they offer crucial help during earthquakes, tsunamis, wars, and pandemics. But with so many ailing areas in need of assistance, how do these organizations decide where to go—and who gets the aid? In The Good Project, Monika Krause dives into the intricacies of the decision-making process at NGOs and uncovers a basic truth: It may be the case that relief agencies try to help people but, in practical terms, the main focus of their work is to produce projects. Agencies sell projects to key institutional donors, and in the process the project and its beneficiaries become commodities. In an effort to guarantee a successful project, organizations are incentivized to help those who are easy to help, while those who are hardest to help often receive no assistance at all. The poorest of the world are made to compete against each other to become projects—and in exchange they offer legitimacy to aid agencies and donor governments. Sure to be controversial, The Good Project offers a provocative new perspective on how NGOs succeed and fail on a local and global level.

Managing Upward and Downward Accountability in an International Development Project - A Case Study of a World Bank Telecommunications Infrastructure Project in Benin - Kolker, Eva; Kulldorff, Catharina (Master's Thesis, Stockholm School of Economics, 2013)
Keywords: Downward accountability; Upward accountability

The Samaritan's Dilemma: The Political Economy of Development Aid - Gibson, Clark C.; Andersson, Krister; Ostrom, Elinor; Shivakumar, Sujai (Oxford University Press, 2005)
What's wrong with foreign aid? Many policymakers, aid practitioners, and scholars have called into question its ability to increase economic growth, alleviate poverty, or promote social development. At the macro level, only tenuous links between development aid and improved living conditions have been found. At the micro level, only a few programs outlast donor support and even fewer appear to achieve lasting improvements. The authors of this book argue that much of aid's failure is related to the institutions that structure its delivery. These institutions govern the complex relationships between the main actors in the aid delivery system and often generate a series of perverse incentives that promote inefficient and unsustainable outcomes. In their analysis, the authors apply the theoretical insights of the new institutional economics to several settings. First, they investigate the institutions of Sida, the Swedish aid agency, to analyze how that aid agency's institutions can produce incentives inimical to desired outcomes, contrary to the desires of its own staff. Second, the authors use cases from India, a country with low aid dependence, and Zambia, a country with high aid dependence, to explore how institutions on the ground in recipient countries also mediate the effectiveness of aid. Throughout the book, the authors offer suggestions about how to improve aid's effectiveness. These suggestions include how to structure evaluations in order to improve outcomes, how to employ agency staff to gain from their on-the-ground experience, and how to engage stakeholders as "owners" in the design, resource mobilization, learning, and evaluation processes of development assistance programs.

Participation and accountability in development management - Brett, E. A. (The Journal of Development Studies, 2003)
This article critically reviews the role of participatory theory in managing development projects and programmes in poor countries. Participation has emerged in response to global demands for greater individual and social control over the activities of state and private agencies, and especially to the manifest failures of traditional ‘top-down’ management systems in LDCs. Claims made on behalf of these participatory methodologies are critically reviewed and a distinction is drawn between strong and weak versions of the theory. Empirical evidence is then considered to evaluate the effectiveness of these methodologies, using long-standing insights of social science theory to show that participation can succeed for specific kinds of projects and programmes in favourable circumstances, but is unsuitable for many others. It commonly fails in contexts where local conditions make co-operative and collective action very difficult, or where it is manipulated by implementing agencies to justify their own actions or poor performance.

Evaluating the ‘logical framework approach’ towards learning-oriented development evaluation - Gasper, Des (Public Administration and Development, 2000)
The logical framework approach has spread enormously, including increasingly to stages of review and evaluation. Yet it has had little systematic evaluation itself. Survey of available materials indicates several recurrent failings, some less easily countered than others. In particular: focus on achievement of intended effects by intended routes makes logframes a very limiting tool in evaluation; an assumption of consensual project objectives often becomes problematic in public and inter-organizational projects; and automatic choice of an audit form of accountability as the priority in evaluations can be at the expense of evaluation as learning.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/1099-162X%28200002%2920%3A1%3C17%3A%3AAID-PAD89%3E3.0.CO%3B2-5

Trapped in a Treadmill: Bureaucratic Constraints on Aid Programs - Hoben, Allen (Harvard International Review, 1992)

Community Organization and Rural Development: A Learning Process Approach - Korten, David C. (Public Administration Review, 1980)

Inside Foreign Aid - Tendler, Judith (The Johns Hopkins University Press, 1975)
A classic, important study in the anthropology of development, grounded in the author's own work within USAID, and analysis of the organizational and institutional pressures that constrain and shape development agency employees' cognition and action.
Keywords: IMPORTANT